The Syntabulin-Syntaxin 1 Axis in Autism: Insights into Neuronal Excitation/ Inhibition Balance - Bittmann, Stefan (Medical Science: Trends and Innovations Vol. 6, 2025)
Autism is a complex developmental disorder that affects the central nervous system, leading to disturbances in relationships and communication with other people. Synaptic cargo vesicles containing presynaptic proteins are transported from the neuronal cell body to the neuronal terminal region to have functional roles in active zone formation. Former research studies showed altered levels of up to 25 different synaptic proteins with a special focus on SNAP47, GRIA3/4, GAP43, synaptotagmin 2, LRFN2, SV2C and syntabulin. Syntabulin works as a key component gene of membranous cargoes and motor-cargo interactions are not completely understood to date. Recent research identified a syntaxin-1-binding protein called syntabulin. Syntabulin links syntaxin-containing vesicles to microtubules and moves with syntaxin in neuronal brain processes. Knocking down syntabulin expression or disrupting the syntabulin-syntaxin interaction hinders the attachment of syntaxin-cargo vesicles to microtubules and reduces syntaxin-1 distribution in neuronal processes. Conventional kinesin I heavy chain binds to syntabulin and associates with syntabulin-linked syntaxin vesicles in vivo. Syntabulin could play an important role as a linker molecule that connects syntaxin-cargo vesicles to kinesin I, facilitating the transportation of syntaxin-1 to neuronal processes. Syntabulin regulates neuronal excitatory and inhibitory imbalance by transporting syntaxin 1 B, more than syntaxin 1A, to the presynaptic membrane formation. The gene for Syntabulin is found on human chromosome 8q23.2, in mouse on chromosome 15. Moreover, the exact role of syntaxin 1 A and 1B is of utmost importance in autism spectrum disorders. This review sheds light on the role of syntabulin- syntaxin 1A/B axis and mentions different synaptic cargo transporters which could play important roles in the pathogenesis of autism spectrum disorders in childhood. Further molecular research should focus on studying synaptopathies in autism spectrum disorders to develop new hypotheses for pharmaceutical interventions.